Personality traits predict regression of pelvic girdle pain after pregnancy: a longitudinal follow-up study - Tang Xiangsheng; Gong Long; Shi Yingying; An Xiao; Yi Ping; Tan Mingsheng (BMC, 2021)
Abstract Background Pelvic girdle pain (PGP) is a multifactorial condition with a partly unknown etiology. This condition can be mentally and physically compromising both during and after pregnancy. To provide all-around preventive measures to improve the recovery from PGP, it is a necessity for obstetricians and orthopaedists to develop predictive studies about the worse prognosis for this condition. Therefore, this study aims to determine whether personality traits can predict the consequences of long-term pregnancy-related PGP. Methods This was a prospective study conducted from January 2015 to August 2018. A total of 387 pregnant women were enrolled in this study. According to whether they had experienced PGP during the past 4 weeks, the subjects were classified into no PGP and PGP groups. Persistent PGP after the pregnancy was defined as a recurrent or continuous visual analog score (VAS) pain rating of ≥3 for more than 1 week. The Quick Big Five Personality Test (QBFPT) was used to assess personality traits. Data were obtained by mail or in the clinic. The authors collected data including age, BMI, educational level, annual household income, cesarean delivery, breastfeeding, unexpected sex of the baby, parity, sick leave, no or rare ability to take rest breaks at work, and PGP in the previous pregnancy. Results Of 387 included women, 264 subjects experienced PGP during the pregnancy with a mean age of 26.3 ± 4.5 years. A total of 80 of 264 (30.3%) women experienced persistent PGP after the pregnancy. Persistent PGP after the pregnancy was associated with higher levels of neuroticism (OR = 2.12, P = 0.001). Comparing women with persistent PGP, those who reported higher levels of extraversion and conscientiousness were more likely to recover from this condition (OR = 0.65, P = 0.001; OR = 0.78, P = 0.010, respectively). Besides, neuroticism was positively associated with higher pain scores (r = 0.52, P = 0.005). However, extraversion and conscientiousness domains showed negative correlations with pain score (r = − 0.48, P = 0.003; r = − 0.36, P = 0.001). Conclusions Personality traits were significantly associated with the outcomes of PGP.